Molecular association of pathogenicity and resistance to multiple antimicrobials in Acinetobacter baumannii strains recovered from patients with diverse infectious diseases - Rafaela O. França; Priscila S. Costa; Guilherme Luiz Milanez; Maria Rosa Q. Bomfim; Ricardo Gonçalves; Luiz M. Farias; Vandack Nobre; Simone G. Santos (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT INTRODUCTION: The success of Acinetobacter baumannii infections can be attributed to its various virulence factors and antimicrobial resistance mechanisms. OBJECTIVE: To evaluate the presence and correlation between different resistance and virulence factors in clinical A. baumannii strains. METHODS: Study conducted at a University Hospital in Belo Horizonte, Minas Gerais, Brazil. The confirmation of Acinetobacter baumannii-calcoaceticus complex was performed by detecting the blaOXA-51 gene through the polymerase chain reaction (PCR), as well as the search for genes: blaOXA-23, 24, 58, 143, blaVIM-1, csuE, ompA and ISAba1. Antimicrobials and metallo-betalactamase (MβL) expression were evaluated by E-test®; and genetic diversity, by enterobacterial repetitive intergenic consensus (ERIC)-PCR. Biofilm formation was classified into four categories according to the mean optical density obtained. RESULTS: 98.4% (61/62) of the strains were resistant to meropenem; 71%, to ceftazidime; and 61.3%, to ampicillin-sulbactam; while 98.4% were sensitive to polymyxin B; and 48.4%, to tigecycline. The production of MβL was detected in 95.2% of the strains. The blaOXA-51 gene was detected in all strains tested; blaVIM-1, in 83.9%; and ISAba1, in 90.3%. On the other hand, the csuE and ompA genes were present in 43.5% and 53.2% of the strains, respectively. CONCLUSION: There was a possible correlation between gentamicin resistant samples and those that were positive for the ompA gene. The csuE gene correlated positively with ISAba1.